STI-prevalence and differences in social background and sexual behavior among urban and rural young women in Uganda - Darj, Elisabeth; Mirembe, Florence M.; Råssjö, Eva-Britta (Sexual & Reproductive Healthcare, 2010)
Adolescents in Uganda carry a heavy burden of reproductive health problems. Different environment creates different problems. Objectives: To study the prevalence of STI and to compare social and behavioral risk factors for Neisseria gonorrhoea (NG) and Chlamydia trachomatis (CT) among sexually experienced young women in one urban and one rural area in Uganda. Methods: Consenting, sexually experienced women, below 20 years, visiting two different youth clinics were asked about social background, genital symptoms and sexual experiences. Vaginal samples were taken for NG and CT and analyzed by PCR.
Keywords: Adolescents; Sexual behavior; Urban Rural STI HIV